2005
DOI: 10.1111/j.1440-172x.2005.00532.x
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ moral agency in negotiating parental participation in care

Abstract: The purpose of this study was to investigate the issues for nurses in facilitating parental participation in the care of the hospitalized child. A qualitative study informed by grounded theory was undertaken. Nine nurses were recruited from an acute, high-dependency, 23-bed paediatric cardiac/renal unit in Melbourne, Australia. Data collection involved individual semistructured interviews, hospital policies related to family-centred care and a focus group interview. Constant comparative analysis was undertaken… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 20 publications
(35 reference statements)
1
37
0
3
Order By: Relevance
“…Four of the papers discussed the role of the nurse and family in the PICU (Martens et al . , O'Haire & Blackford , Ames et al . , Macdonald et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Four of the papers discussed the role of the nurse and family in the PICU (Martens et al . , O'Haire & Blackford , Ames et al . , Macdonald et al .…”
Section: Resultsmentioning
confidence: 99%
“…The researcher bias was also not discussed in any of the qualitative studies that used interviews or observation. The main strengths of the studies assessed surround either multimodal data collection (Jefferson & Paterson , O'Haire & Blackford , Aronson et al . , Cameron et al .…”
Section: Methodsmentioning
confidence: 99%
“…Although there is a growing body of literature on the views of nurses and parents about their respective roles in caring for hospitalised children, there seems to be no clear consensus as to what these roles are or how they should be negotiated (O'Haire and Blackford 2005). A study by Hughes (2007) found that nurses often assumed parents would wish to participate actively in the nursing care of their hospitalised child.…”
Section: The 1959 Ministry Of Health Report Entitledmentioning
confidence: 99%
“…These authors assert that negotiation depends on the development of relationships between the family and health care providers (Corlett & Twycross, 2006b). In fact, power struggles are still associated with parental participation in their children's care (Coyne, 2008a;Coyne & Cowley, 2007;Lee, 2007;Martenson et al, 2009;McPherson et al, 2011;Priddis & Shields, 2011) and a gap exists between nurses' expectations and parents' attitudes (O'Haire & Blackford, 2005;Young et al, 2006).…”
Section: Models Of Partnershipmentioning
confidence: 96%